2023
DOI: 10.1093/jnci/djad020
|View full text |Cite
|
Sign up to set email alerts
|

Changes in survival in de novo metastatic cancer in an era of new medicines

Abstract: Background Over the past decades, the therapeutic landscape has markedly changed for patients with metastatic solid cancer, yet few studies have evaluated its effect on population-based survival. The objective of this study was to evaluate the change in survival of patients with de novo metastatic solid cancers during the last 30 years. Methods For this retrospective study, data from almost 2 million patients diagnosed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…This cross-sectional study found that median OS in de novo mHSPC was similar in SEER and VHA and had improved significantly in the US population from 2000 to 2019, particularly in patients younger than 70 years. The improvements in OS mirror those observed in other countries and are likely due to the increased use of combination therapy . Our results suggest that new treatment paradigms may contribute to longer OS in clinical practice, which is the ideal setting to measure improvements in outcomes as treatments change.…”
Section: Discussionsupporting
confidence: 71%
“…This cross-sectional study found that median OS in de novo mHSPC was similar in SEER and VHA and had improved significantly in the US population from 2000 to 2019, particularly in patients younger than 70 years. The improvements in OS mirror those observed in other countries and are likely due to the increased use of combination therapy . Our results suggest that new treatment paradigms may contribute to longer OS in clinical practice, which is the ideal setting to measure improvements in outcomes as treatments change.…”
Section: Discussionsupporting
confidence: 71%
“…However, the reasons may be more complicated. In the Netherlands, metastatic data are available on all common cancers and the proportion of M1 of all PC varies extensively over time 29 . It was over 25% around 1990 and then decreased to 13% around 2010 and increased again towards 2018 to almost 20% 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, metastatic data are available on all common cancers and the proportion of M1 of all PC varies extensively over time 29 . It was over 25% around 1990 and then decreased to 13% around 2010 and increased again towards 2018 to almost 20% 29 . PSA testing for PC started in the Netherlands at around 1990 similar to Sweden 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients with incurable solid cancer still die within months of being diagnosed, others may live for a considerable time 22. A retrospective study in the Netherlands that included almost two million patients with solid cancer showed a median survival of less than 7 months in patients with incurable solid cancer 38. Research investigating the actual increase of survival rates within cancer care has been limited to specific cancer types, and with specific genetic mutations or rearrangements (table 1).…”
Section: What Are the Limitations In Interpreting Illness Trajectories?mentioning
confidence: 99%